Prospective randomized clinical trial of a change in gastric emptying and nutritional status after a pylorus‐preserving pancreaticoduodenectomy: comparison between an antecolic and a vertical retrocolic duodenojejunostomy. Issue 4 (29th August 2013) - Imamura, Naoya; Chijiiwa, Kazuo; Ohuchida, Jiro; Hiyoshi, Masahide; Nagano, Motoaki; Otani, Kazuhiro; Kondo, Kazuhiro
Abstract Background Although an antecolic duodenojejunostomy was reported to reduce post‐operative delayed gastric emptying (DGE) compared with a retrocolic duodenojejunostomy after a pylorus‐preserving pancreaticoduodenectomy (PPPD), the long‐term effects of these procedures have rarely been studied. The aim of this prospective, randomized, clinical trial was to investigate the influence of the reconstruction route on post‐operative gastric emptying and nutrition. Methods Reconstruction was performed in 116 patients with an antecolic duodenojejunostomy (A group, n = 58) or a vertical retrocolic duodenojejunostomy (VR group, n = 58). Post‐operative complications, including DGE, gastric emptying variables assessed by 13C‐acetate breath test and nutrition, were compared between the two groups for 1 year post‐operatively. Results The incidence of DGE was not significantly different between the procedures (A group: 12.1%; VR group: 20.7%, P = 0.316). At post‐operative month 1, gastric emptying was prolonged in the VR versus the A group but not significantly so. At post‐operative month 6, gastric emptying was accelerated significantly in the A versus the VR group. Post‐operative weight recovery was significantly better in the VR versus the A group at post‐operative month 12 (percentage of pre‐operative weight, A group: 93.8 ± 1.2%; VR group: 98.5 ± 1.3%, P = 0.015). Conclusions A vertical retrocolic duodenojejunostomy was an acceptable procedure for the lower incidence of DGE and may contribute to better weight gain affected by moderate gastric emptying.